SHEAR STRENGTH CHARACTERISTICS OF PPF-TREATED GYPSUM SOIL PREPARED AT VARIOUS MAXIMUM DENSITIES - Farouk M. Muhauwiss; Ahmed H. Salh (Journal Park Publishing, 2022)
The problem with gypsum soils is that they have a high bearing capacity unless water reaches them. Nonetheless, it will create air spaces or cavities in these soils beneath the inundation states. It may collapse under the influence of the origin load and without additional external loads.
Keywords: Gypseous soil _ Direct Shear Strength_ polypropylene fiber_ various densities.